Implementation of The Pancasila Student Profile in Elementary School Students Inpres: A Study of Religious Activities - Yadanfle, Yohan; Faizin, Muhammad; Simatupang, Ernawati (Jurnal Riset dan Inovasi Pembelajaran, 2025)
This study intends to elucidate the effects of implementing the Pancasila student profile on the religious activities of elementary school students. The approach employed to cultivate student character in alignment with the Pancasila student profile, together with the facilitating aspects and challenges encountered in the execution of the Pancasila student profile within religious activities. This research is qualitative and descriptive in nature. The participants of the study included students, instructors, and principals from Elementary School Students Inpres 12 in Sorong Regency. The data collection methods employed in this study were observation, interviews, and documentation. The data analysis methodology employed an interactive paradigm involving data collection, data analysis, report compilation, and conclusion formulation. The findings indicated that the Pancasila student profile influenced the perceptions and outcomes for students at Elementary School Inpres 12. The approach employed to cultivate students into devoted and pious individuals entails spiritual awareness and adherence to God Almighty. Students exhibit noble character in their daily lives by displaying honesty, fairness, tolerance, self-control, and ethical interaction. Contributing elements encompass specialized studies that reinforce the Pancasila student profile. Furthermore, the impediment is the absence of training on the autonomous curriculum for school inhabitants.